Microstructure and compressive properties of directionally solidified Er-bearing TiAl alloy using cold crucible. (5th June 2016) - Wang, Qiang; Ding, Hongsheng; Zhang, Hailong; Liu, Shiqiu; Chen, Ruirun; Guo, Jingjie; Fu, Hengzhi
Abstract: Dual phase γ-TiAl of Ti-47Al-2Nb-2Cr was alloyed by erbium and then prepared by directional solidification using electromagnetic cold crucible. Compression test was performed to determine the work hardening capacity in accordance with microstructures regarding erbium additions. The directionally solidified columnar grains were refined by 0.2 at.% erbium in comparison to those without erbium, while columnar to equiaxed transition (CET) happened in the case of 0.8 at.% erbium. Since oxygen has extremely strong affinity to erbium, oxygen dissolved in the TiAl matrix decreased from 940 ppm to 560 ppm by internally oxidizing of erbium. The scanning electron microscopy characterization revealed that the Er2 O3 particles were dispersed uniformly in the (α2  + γ) lamellae. Arising from the loss of interstitial oxygen in the matrix, stacking fault energy of the h.c.p. phase (α2 or α) was decreased which resulted in increasing nucleation sites of γ phase. Then the γ lamellae were refined in the Er-bearing alloys. During the compression test, the work hardening capacity (Hc ) of the 0.2 at.% Er-bearing alloy was improved at strain rate ε ̇ of 10 − 1 –10 − 3  s − 1, which could be fitted as H c = 1.66 ε ̇ − 0.05 . Besides, the governing deformation mechanism of the Er-bearing TiAl alloy was the same as the Er-free TiAl alloy according to the strain rate sensitivity results. Graphical abstract: Highlights: Directionally solidified grains and lamellar laths are both refined significantly by erbium additive in TiAl alloy. Oxygen dissolved in the TiAl matrix decreased from 940 ppm to 560 ppm by internally oxidizing of erbium. Less oxygen results in lower stacking fault energy of h.c.p. phase (α) and promotes thin γ laths. Work hardening capacity is improved with 0.2 at.% erbium additive at strain rate of 10 − 1 –10 − 3  s − 1 .